Ultra-trace metallic element detection in liquid samples using laser induced breakdown spectroscopy based on matrix conversion and crosslinked PVA polymer membrane. Issue 8 (15th June 2016) - Lin, Qingyu; Han, Xiaodan; Wang, Jie; Wei, Zhimei; Liu, Kunping; Duan, Yixiang
Abstract : A novel, sensitive method based on crosslinked polyvinyl alcohol (PVA) was developed for determining trace-amounts of metallic elements in liquid samples using laser induced breakdown spectroscopy (LIBS). Abstract : A novel method with high sensitivity was developed for determining ultra-trace-amounts of metallic elements in liquids by LIBS analysis, based on crosslinked polyvinyl alcohol (PVA) supporting material. In this newly proposed approach, an aqueous solution sample was intensively mixed with PVA solution leading to phase conversion, which is distinguished from the desiccation process on a solid supporter as reported in the literature of liquid-to-solid conversion for LIBS analysis. The analytes were distributed in a thin PVA film (0.34 mm) as a result of crosslinking the polymer materials, and thereby the plasma signals generated by laser pulse were stronger and a lower amount of solid supporter was needed compared to traditional methods. Due to the low PVA thermal decomposition temperature, laser generated plasma energy was effectively utilized for not only ablating the sample, but rather exciting analytes within the sample. The limits of detection for Ag, Cu, Cr, Pb, Ni, Co and Cd obtained in this study were 1 ng mL −1, 8 ng mL −1, 16 ng mL −1, 1 μg mL −1, 1 μg mL −1, 2 μg mL −1 and 5 μg mL −1, respectively, which showed great improvement compared with those from direct liquid analysis by LIBS. The satisfactory figures of merits of the proposed method, including linearity, reproducibility and accuracy, were also obtained with the optimal experimental parameters. This unique method takes advantage of mixing an aqueous solution sample with supporter material in a liquid phase and it has characteristics of fast, simple and sensitive analysis for liquid sample compared with conventional liquid-to-solid conversion methods for LIBS.